Structural Analysis using X-Ray Diffraction and FTIR Spectroscopic Studies on Mn2+ Substituted CaWO4 Materials Synthesized by Coprecipitation Method - Rao, M. Jaganadha; Murthy, K.S.R.; Shankar Kumar, Ch. Ravi; Jha, Anjali; Choudary, G.S.V.R.K.; Varma, M. Chaitanya (Asian Journal of Chemistry, 2019)
Present day technology requires synthesis of materials with low energy consumption, free mercury pollution and its reliability. A novel material with control of crystallite size, composition and simple for white light relies in synthesis of materials. The present focus of article attributes series of manganese doped Ca1-xMnxWO4 luminescent materials with co-precipitation method. Reported studies attempts with change in structure of calcium tungstate (CaWO4) are observed with dopants like Eu3+, Eu2+, Tb3+, etc. However the effect of Mn2+ on structural properties of CaWO4 are quite interesting. The synthesized samples were characterized with X-ray diffraction for lattice parameters, crystallite size and FTIR studies for bonding mechanism of O-W-O stretching and W-O-W bridge bond. Rietveld profile refinement of XRD patterns using MAUD program Ca1-xMnxWO4 revealed the Scheelite type structure with C4h point group and I41/a space group. Characterization studies reveal that doping of Mn2+ doping upto 0.1 in place of Ca2+ will not change the phase of Scheelite structure.